Ответ:
3x-5_x+11=2х-5+11=2х+6
2х=6
х=6/2
х=3
B) 7 2x-1_3x+2=7х-3х-1+2=5х+1
5х=1
х=1/5
х=0,2
г) 4x-5_6x+11 = 3 x+1 10 +x= 5 x-7 5 -2
4х-6х-5+11=4х+110=5х-77
-2х+6=4х+110=5х-77
-2х-4х-5х=110-77-6
-11х=27
х=27/(-11)
х=2,45
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
3x-5_x+11=2х-5+11=2х+6
2х=6
х=6/2
х=3
B) 7 2x-1_3x+2=7х-3х-1+2=5х+1
5х=1
х=1/5
х=0,2
г) 4x-5_6x+11 = 3 x+1 10 +x= 5 x-7 5 -2
4х-6х-5+11=4х+110=5х-77
-2х+6=4х+110=5х-77
-2х-4х-5х=110-77-6
-11х=27
х=27/(-11)
х=2,45
Пошаговое объяснение: